Vascular Injury Accompanying Displaced Proximal Humeral Fractures: Two Cases and a Review of the Literature - Martijn Hofman; Jochen Grommes; Gabriele A. Krombach; Bernhard Schmidt-Rohlfing (Emergency Medicine International)
We present two cases in which displaced proximal humeral fractures are accompanied by vascular injury. These Injuries are very rare but severe and the accompanying vascular impairment can have great clinical consequences. Therefore, we try to emphasize on the importance of thorough and accurate diagnostics, because it is obligatory for early diagnosis and improving the eventual outcome of these injuries. The specific order in treatment (internal fixation first or vascular repair first) depends on the severity of the accompanying vascular injury. The increasing use of endovascular procedures to treat vascular lesions is a very interesting development with several advantages, especially in elderly and multimorbid patients.